302 Alcohol outlet density and hospital admissions for alcohol-related injury: an electronic record-linked cohort study. (1st September 2016) - Rodgers, Sarah; Farewell, Daniel; Dunstan, Frank; White, James; Orford, Scott; Morgan, Jennifer; Fry, Richard; Lyons, Ronan; Fone, David
Abstract : Background: Little is known on the longitudinal relationship between alcohol availability and the risk of admission to hospital for an alcohol-related injury. We aimed to quantify this relationship using observational record-linked data in a total adult population cohort in Wales, UK; population 2.5 million aged 16 years and over. Methods: Data sources included licensed outlets held by the 22 local authorities in Wales under The Licensing Act 2003 for each quarter between 2006 and 2011. Alcohol outlet density was estimated for Census geography small areas (n = 1896 divided into quintiles of equal counts) based on the mean network walking distances between each household and alcohol outlet within a 10 minute walk. Hospital admissions 2006–2011 from the Patient Episode Database for Wales (PEDW) for wholly alcohol-related conditions were anonymously record-linked to the Welsh Demographic Service age-sex register within the Secure Anonymised Information Linkage Databank. Injury admissions were defined by ICD-10 codes S00-99 and T00-19 linked to an alcohol code. Longitudinal statistical analysis used Cox regression models of hospital admissions as a function of outlet density at baseline, adjusting for confounding variables of age, sex and small area deprivation and settlement type, and censoring for death, migration and other cause admission. Results: Alcohol outlet density at baseline was significantly associated with emergency hospital admission; the hazard ratio (HR) of an alcohol-related admission (n = 25, 722) for living in the highest compared with the lowest quintile of outlet density was 1.17 (95% CI: 1.11, 1.23). The risk was higher for alcohol-related admissions with injury (n = 4, 308; HR 1.27, 95% CI: 1.13, 1.42). Conclusions: Higher alcohol outlet availability was associated with more emergency hospital admissions for alcohol-related injury. This suggests that restricting the density of alcohol outlets within walking distance from home may improve population health.